2019
DOI: 10.1039/c9cc03282g
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of trifluoromethyl amines and perfluoroalkyl amines with CF3SO2Na and RfSO2Na

Abstract: Novel use of CF3SO2Na and RfSO2Na for the synthesis of trifluoromethyl amines and perfluoroalkyl amines was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…For a real test of our procedure, we chose t ert ‐butyl piperazine‐1‐carboxylate ( 12 ) that had been used previously, [2,9] and successfully obtained the N ‐trifluoromethyl analogue 13 in decent yields with our method. In contrast to the former reports, in which the product was described as an oil, we could isolate it as a crystalline colorless substance, clearly demonstrating one of the advantages of our method for this particular substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a real test of our procedure, we chose t ert ‐butyl piperazine‐1‐carboxylate ( 12 ) that had been used previously, [2,9] and successfully obtained the N ‐trifluoromethyl analogue 13 in decent yields with our method. In contrast to the former reports, in which the product was described as an oil, we could isolate it as a crystalline colorless substance, clearly demonstrating one of the advantages of our method for this particular substrate.…”
Section: Resultsmentioning
confidence: 99%
“…A similar process had been observed previously for the synthesis of CF 3 -ethers, [4b,8] however, to the best of our knowl-edge, the reaction of monomeric N-dithiocarbamate-organyls and their conversion via AgF to N-CF 3 groups had not been reported so far. [1b] For a real test of our procedure, we chose tert-butyl piperazine-1-carboxylate (12) that had been used previously, [2,9] and successfully obtained the N-trifluoromethyl analogue 13 in decent yields with our method. In contrast to the former reports, in which the product was described as an oil, we could isolate it as a crystalline colorless substance, clearly demonstrating one of the advantages of our method for this particular substrate.…”
Section: Chemistryselectmentioning
confidence: 99%
“…In contrast to perfluoroalkyl and perfluoroalkoxy groups, the chemistry of related perfluoroalkyl nitrogen substituents has been studied to a much lesser extent. Some synthetic strategies towards N ‐trifluoromethylamines and related N ‐perfluoroalkylnitrogen derivates have been developed in recent years [28–38] . Efficient strategies towards N , N ‐bis(perfluoroalkyl)nitrogen compounds remain scarce, presumably, because of the lack of suitable starting materials [18,39–40] .…”
Section: Figurementioning
confidence: 99%
“…Some synthetic strategies towards N ‐trifluoromethylamines and related N ‐perfluoroalkylnitrogen derivates have been developed in recent years. [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] Efficient strategies towards N , N ‐bis(perfluoroalkyl)nitrogen compounds remain scarce, presumably, because of the lack of suitable starting materials. [ 18 , 39 , 40 ] Especially the N , N ‐bis(trifluoromethyl)amino group is of interest as its organic derivatives are known to exhibit high stability, for example against acids and bases,[ 1 , 41 ] and because its potential as substituent in pharmaceuticals was demonstrated, earlier.…”
mentioning
confidence: 99%
“…The latter can also be generated starting from AgSCF 3 in conjunction with potassium bromide (Scheme , III ). More recently, the group of Jiang and Yi demonstrated that the Langlois reagent could also be used in conjunction with triphenylphosphine to form thiocarbamoyl fluorides (Scheme , IV ) . In this context, we thought that the straightforward synthesis of thiocarbamoyl fluoride through fluorinative desulfurization would constitute an attractive option for the access thiocarbamoyl fluorides.…”
Section: Introductionmentioning
confidence: 99%